Proceedings of the Twenty-Seventh Annual ACM-SIAM Symposium on Discrete Algorithms 2015
DOI: 10.1137/1.9781611974331.ch108
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and Rigidity in a Regular Stochastic Block Model

Abstract: The stochastic block model is a natural model for studying community detection in random networks. Its clustering properties have been extensively studied in the statistics, physics and computer science literature. Recently this area has experienced major mathematical breakthroughs, particularly for the binary (two-community) version, see [24, 25, 20]. In this paper, we introduce a variant of the binary model which we call the regular stochastic block model (RSBM). We prove rigidity of this model by showing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…e distribution of ϑ(G) for the Erdős-Rényi graph G = G(n, p) and the random dregular graph G = G n,d were studied in [20]. In particular, that work showed that when d is sufficiently 1 ese models are not to be confused with a stricter model, where for some constants qrs each vertex in group r has exactly qrs neighbors in group s [18,23,53,15]. Our model only constrains the total number of edges within or between groups.…”
mentioning
confidence: 99%
“…e distribution of ϑ(G) for the Erdős-Rényi graph G = G(n, p) and the random dregular graph G = G n,d were studied in [20]. In particular, that work showed that when d is sufficiently 1 ese models are not to be confused with a stricter model, where for some constants qrs each vertex in group r has exactly qrs neighbors in group s [18,23,53,15]. Our model only constrains the total number of edges within or between groups.…”
mentioning
confidence: 99%
“…In SBM there exists a sharp transition in the assortativity parameter, first conjectured in [31] and later proved rigorously in a series of works that demonstrate both that asymptotically (i) below such threshold, recovery is information theoretically impossible [19] while (ii) above, an efficient algorithm finds a partition with positive overlap with the original one [20,21]. In this work, it is shown that the regularity condition, as also found in [13], substantially change the detectability properties of the ensemble.…”
Section: The Inference Problemmentioning
confidence: 56%
“…This class of random graph models has been first analyzed in [14] in a dense approximation, in [15] for the first time under the name of equitable graphs and under the name microcanonical stochastic block model in [17]. In [13] it has been shown that equitable graphs with two-equallysized communities have a unique partition almost surely in the large size limit, that an efficient algorithm can be derived in a large region of the ensemble's parameters, and that full recovery of communities can be obtained starting from a group assignment with an extensive overlap with the original partition. In this paper, spectral theory of random graphs is used to disentangle noise and signal in equitable graphs, and an efficient algorithm for full recovery of communities is proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Arguably the most popular model for community detection is the stochastic block model (SBM), where any two vertices within the same cluster or across different clusters are connected by an edge with probability p or q, respectively. The asymptotic limits for both exact and partial recovery have been extensively studied [1,2,10,26,38,39,57,60]. We note, however, that the primary focus of community detection lies in the sparse regime p; q 1=n or logarithmic sparse regime (i.e., p; q log n=n), which is in contrast to the joint alignment problem in which the measurements are often considerably denser.…”
Section: Otherwise;mentioning
confidence: 99%